Evaluation of the antitumor activity of NOV202, a novel microtubule targeting and vascular disrupting agent - Rickardson L; Kutvonen E; Orasniemi S; Högberg M; Kallio MJ; Rehnmark S (Dove Medical Press, 2017)
Linda Rickardson,1 Emma Kutvonen,2 Satu Orasniemi,2 Marita Högberg,1 Marko J Kallio,2,3 Stefan Rehnmark1 1Noviga Research AB, Södertälje, Sweden; 2Department of Physiology, Institute of Biomedicine, University of Turku, 3Centre for Biotechnology, University of Turku, Turku, Finland Purpose: Overall, ~65% of patients diagnosed with advanced ovarian cancer (OC) will relapse after primary surgery and adjuvant first-line platinum- and taxane-based chemotherapy. Significant improvements in the treatment of OC are expected from the development of novel compounds having combined cytotoxic and antiangiogenic properties that make them effective on refractory tumors. Methods: Permeability of NOV202 was determined with Caco-2 monolayer assay. The compound’s pharmacokinetic profile and plasma:brain distribution were assessed in male C57Bl/6 mice. The compound’s impacts on tubulin, microtubules and cell cycle were investigated by using in vitro tubulin polymerization assay, cell-based immunofluorescence and live cell microscopy. The IC50 concentrations of NOV202 were assessed in a panel of eight cancer cell lines. Impact of the compound on vascular tube formation was determined using the StemKit and Chick chorioallantoic membrane assays. The in vivo efficacy of the compound was analyzed with an OC xenograft mouse model. Results: NOV202 was found to suppress cancer cell proliferation at low nanomolar concentrations (IC50 2.3–12.0 nM) and showed equal efficacy between OC cell line A2780 (IC50 2.4 nM) and its multidrug-resistant subline A2780/Adr (IC50 2.3 nM). Mechanistically, NOV202 targeted tubulin polymerization in vitro in a dose-dependent manner and in cells induced an M phase arrest. In vivo, NOV202 caused a dose-dependent reduction of tumor mass in an A2780 xenograft model, which at the highest dose (40 mg/kg) was comparable to the effect of paclitaxel (24 mg/kg). Interestingly, NOV202 exhibited vascular disrupting properties that were similar to the effects of Combretastatin A4. Conclusion: NOV202 is a novel tubulin and vascular targeting agent that shows strong anticancer efficacy in cells and OC xenograft models. The finding that the compound induced significantly more cell death in Pgp/MDR1 overexpressing OC cells compared to vincristine and paclitaxel warrants further development of the compound as a new therapy for OC patients with treatment refractory tumors and/or relapsing disease. Keywords: ovarian cancer, NOV202, microtubule-targeting agent, vascular disruption, M phase arrest, multidrug resistance